Partial replacement of K by Na in Eucalyptus species under water restriction: characterization of nutritional, physiological, biochemical, molecular and morphoanatomical drought tolerance mechanisms - Mateus, Níkolas de Souza (2024)
This thesis aimed to evaluate the replacement of potassium (K) by sodium (Na) in Eucalyptus species under water restriction. In the first chapter, a literature review introduces fertilization as an essential management practice to sustain the high yield of planted forests, and suggest the replacement of K by Na as a strategy to increase plant tolerance to drought stress. In the second chapter, morphological, nutritional, physiological, biochemical, molecular, and anatomical functional traits were explored to investigate the drought tolerance mechanisms triggered by the partial replacement of K by Na in Eucalyptus species. We defined the rate 70/30% of K/Na as ideal for Eucalyptus, increasing K-utilization efficiency and promoting partial stomatal closure, consequently improving water status, photosynthetic capacity, photoprotection, and plant growth. In contrast, higher proportions of K replacement by Na led to K deficiency and incomplete stomatal closure, in addition to lower growth. In the third chapter, the replacement of K by Na in xylem embolism resistance of woody species was addressed for the first time in the literature. This study showed that the ideal rate (70/30% K/Na) promoted faster stomatal responses and increased xylem embolism resistance, as well as biomass production and consequently plant water consumption. However, it also indicated that fertilized plants operate close to their hydraulic limits to maximize CO2 assimilation, a strategy that can increase the negative effects of water drought and lead to hydraulic failure. Finally, this thesis supports the feasibility of using Na as a non-commercial alternative, reducing the dependence on K-based fertilizers and increasing the profitability of the forestry sector, given the potential of partial K replacement by Na in maximizing productivity and mitigating the impacts of drought stress.